3D bioprinting of a trachea-mimetic cellular construct of a clinically relevant size. (December 2021) - Park, Jeong Hun; Ahn, Minjun; Park, Sun Hwa; Kim, Hyeonji; Bae, Mihyeon; Park, Wonbin; Hollister, Scott J.; Kim, Sung Won; Cho, Dong-Woo
Abstract: Despite notable advances in extrusion-based 3D bioprinting, it remains a challenge to create a clinically-sized cellular construct using extrusion-based 3D printing due to long printing times adversely affecting cell viability and functionality. Here, we present an advanced extrusion-based 3D bioprinting strategy composed of a two-step printing process to facilitate creation of a trachea-mimetic cellular construct of clinically relevant size. A porous bellows framework is first printed using typical extrusion-based 3D printing. Selective printing of cellular components, such as cartilage rings and epithelium lining, is then performed on the outer grooves and inner surface of the bellows framework by a rotational printing process. With this strategy, 3D bioprinting of a trachea-mimetic cellular construct of clinically relevant size is achieved in significantly less total printing time compared to a typical extrusion-based 3D bioprinting strategy which requires printing of an additional sacrificial material. Tracheal cartilage formation was successfully demonstrated in a nude mouse model through a subcutaneous implantation study of trachea-mimetic cellular constructs wrapped with a sinusoidal-patterned tubular mesh preventing rapid resorption of cartilage rings in vivo . This two-step 3D bioprinting for a trachea-mimetic cellular construct of clinically relevant size can provide a fundamental step towards clinical translation of 3D bioprinting based tracheal reconstruction.